THE ROLE OF QUIZIZZ APPLICATION IN LEARNING: A LITERATURE REVIEW - Non Syafriafdi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Sailing through the 21st century, integrating technology into the classroom has become necessary. To ensure successful learning, educators need effective tools that can boost motivation and support student engagement. One of these tools is Quizizz. This research aims to contribute to the thriving research on technology use in education by investigating the role of Quizizz in learning. Employing qualitative design, the method used is library research, which involved reviewing and analyzing existing literature related to Quizizz and its use in educational settings. The research concludes that the Quizizz plays a considerable role in the learning process today. It is one of the most appropriate and relevant applications used in learning, particularly for evaluation. Interactive and fun learning experience, active student engagement, instant feedback, and learning personalization are some of the factors that make Quizizz a very powerful tool to increase student learning motivation and interest, which naturally also results in the improvement of learning achievement. Moreover, Quizizz's features can also help develop the 21st century skills that are essential for students to have today, particularly critical thinking, communication, and collaboration.